Characterizing the Business Cycles of Emerging Economies - Calderón, Cesar; Fuentes, Rodrigo (2012)
Using the dating algorithm by Harding and Pagan (2002) on a quarterly database for 23 emerging market economies (EMEs) and 12 developed countries over the period 1980.Q1 - 2006.Q2, the authors proceed to characterize and compare the business cycle features of these two groups. They first find that recessions are deeper and more frequent among EMEs (especially, among LAC countries) and that expansions are more sizable and longer (especially, among East Asian countries). After this characterization, this paper explores the linkages between the cost of recessions (as measured by the average annual rate of output loss in the peak-to-trough phase of the cycle) and several country-specific factors. The main findings are: (a) adverse terms of trade shocks raises the cost of recessions in countries with a more open trade regime, deeper financial markets and, surprisingly, a more diversified output structure. (b) U.S. interest rate shocks seem to have a significant impact on the cost of recessions in East Asian countries. (c) Recessions tend to be deeper if they coincide with a sudden stop, but the effect tends to be mitigated in countries with deeper domestic credit markets. (d) Countries with stronger institutions tend to have less costly recessions.